Edible Insects as an Alternative Source of Nutrients: Benefits, Risks, and the Future of Entomophagy in Europe—A Narrative Review - Wojciech Michał Jankowski; Dominik Przychodniak; Weronika Gromek; Emilia Majsiak; Marcin Kurowski (Foods)
According to projections by the Food and Agriculture Organization of the United Nations, the global population will reach 9 billion by 2050. This raises concerns about the ability to feed such a population. In view of the above, it is necessary to search for alternative food sources. Edible insects are rich in complete protein, essential fatty acids, vitamins and micronutrients. Despite this, entomophagy is not common in Europe. In 2021, the European Union approved Acheta domesticus, Tenebrio molitor, Locusta migratoria, and Alphitobius diaperinus for consumption. However, their consumption may also be associated with certain hazards, e.g., food allergies. The purpose of this review is to present existing knowledge, discuss the possible dangers of consuming insects, and identify areas for further research. Studies in Asian populations indicate that edible insects may be responsible for 4.2–19.4% of food allergies and 18% of fatal food-induced anaphylaxis. There are also increasing reports from Europe of food allergies to edible insects. A thorough understanding of allergens, their properties, and the mechanisms of food allergies associated with edible insects’ consumption is essential for ensuring consumers’ safety. In the future, it would be worthwhile to investigate the effects of heat treatment on the allergenicity of insect proteins.